Soul covers rhythm and blues remakes and the struggle for artistic identity : (Aretha Franklin, Al Green, Phoebe Snow) - Awkward, Michael (Refiguring American music, 2007)
"She's the next one" : Aretha Franklin's Unforgettable : a tribute to Dinah Washington and the black women's vocal legacy -- "Something like wholeness" : Al Green's Call me and the struggle for thematic integrity -- "Miss Snow, are you black?" : second childhood and the cultural politics of musical style in the post-civil rights era